2020
DOI: 10.15252/embj.2020104514
|View full text |Cite
|
Sign up to set email alerts
|

m 6 A RNA methyltransferases METTL3/14 regulate immune responses to anti‐PD‐1 therapy

Abstract: An impressive clinical success has been observed in treating a variety of cancers using immunotherapy with programmed cell death-1 (PD-1) checkpoint blockade. However, limited response in most patients treated with anti-PD-1 antibodies remains a challenge, requiring better understanding of molecular mechanisms limiting immunotherapy. In colorectal cancer (CRC) resistant to immunotherapy, mismatch-repair-proficient or microsatellite instability-low (pMMR-MSI-L) tumors have low mutation burden and constitute~85%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
247
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(274 citation statements)
references
References 75 publications
(100 reference statements)
9
247
1
Order By: Relevance
“…In addition, in mismatch-repair-proficient or microsatellite instability-low (pMMR-MSI-L) colorectal cancer and melanoma, the deletion of METTL3 and METTL14 increased the infiltration of CD8+T cells and the secretion of IFN- γ, Cxcl9 and Cxcl10, and enhanced the anti-PD-1 response. The absence of METTL3 and METTL14 reduced the m6A modification of STAT1 and IRF1 mRNA and the YTHDF2-mediated mRNA degradation to increase the levels of STAT1 and IRF1 which participate in IFN- γ-Stat1-Irf1 signal axis and play an important role in anti-PD-1 response ( 110 ).…”
Section: Immunoregulation Of Rna Methylation In Various Cancersmentioning
confidence: 99%
“…In addition, in mismatch-repair-proficient or microsatellite instability-low (pMMR-MSI-L) colorectal cancer and melanoma, the deletion of METTL3 and METTL14 increased the infiltration of CD8+T cells and the secretion of IFN- γ, Cxcl9 and Cxcl10, and enhanced the anti-PD-1 response. The absence of METTL3 and METTL14 reduced the m6A modification of STAT1 and IRF1 mRNA and the YTHDF2-mediated mRNA degradation to increase the levels of STAT1 and IRF1 which participate in IFN- γ-Stat1-Irf1 signal axis and play an important role in anti-PD-1 response ( 110 ).…”
Section: Immunoregulation Of Rna Methylation In Various Cancersmentioning
confidence: 99%
“…The latest studies also revealed the connection between m 6 A regulators and tumor immune-cell infiltration (Han et al, 2019;Li et al, 2020;Wang et al, 2019Wang et al, , 2020Winkler et al, 2019). For example, inhibition of METTL3/14 promoted IFN-γ-STAT1-IRF1 signaling and enhanced response to anti-PD-1 treatment in colorectal cancer (Wang et al, 2020). ALKBH5 inhibitor could heighten the efficacy of cancer immunotherapy (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic modification in m 6 A mediated by these regulators not only plays important roles in the development of oocytes and cerebellum but also plays essential roles in regulating cell proliferation and migration, leading to the malignant progression of various cancers and treatment resistance (Chen et al, 2019;Lan et al, 2019). The latest studies also revealed the connection between m 6 A regulators and tumor immune-cell infiltration (Han et al, 2019;Li et al, 2020;Wang et al, 2019Wang et al, , 2020Winkler et al, 2019). For example, inhibition of METTL3/14 promoted IFN-γ-STAT1-IRF1 signaling and enhanced response to anti-PD-1 treatment in colorectal cancer (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, targeting m 6 A and m 6 A regulators could also be a potential therapeutic strategy for radiotherapy and immunotherapy. A recent study found that the inhibition of METTL3/14 methylation modifications to STAT1 and IRF1 can enhance the sensitivity of anti-PD-1 therapy in pMMR/MSI-L CRC [ 83 ]. So far, no studies have explained the relationship between m 6 A modification and CRC radiotherapy sensitivity.…”
Section: Discussionmentioning
confidence: 99%